Outcomes of Anti-VEGF Therapy in Eyes with Diabetic Macular Edema, Vein Occlusion-Related Macular Edema, and Neovascular Age-Related Macular Degeneration: A Systematic Review - Aldokhail LS; Alhadlaq AM; Alaradi LM; Alaradi LM; AlShaikh FY (Clinical Ophthalmology)
Laila Salah Aldokhail,1 Abdulaziz Mohammad Alhadlaq,2 Lujain Mohamed Alaradi,1 Lamees Mohamed Alaradi,1 Fatimah Yaseen AlShaikh1 1Department of Ophthalmology, College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 2Division of Ophthalmology, Security Forces Hospital, Riyadh, Saudi Arabia, Ophthalmology Department, College of Medicine, Qassim university, Qassim, Saudi ArabiaCorrespondence: Laila Salah Aldokhail, Department of Ophthalmology, College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia, Email Aldokhail.laila@gmail.comBackground: Anti-vascular endothelial growth factor (anti-VEGF) therapy has revolutionized the management of various ocular conditions, including diabetic macular edema (DME), retinal vein occlusion (RVO)-related macular edema (ME), and neovascular age-related macular degeneration (nAMD). However, there remains a need to systematically assess its effectiveness across these distinct conditions.Methodology: A systematic review was conducted to identify studies evaluating the efficacy of anti-VEGF therapy in improving ocular outcomes in patients with DME, RVO-related ME, and nAMD. PubMed, Embase, and Cochrane Library databases were searched for relevant articles published up to 2024. Studies meeting the inclusion criteria were critically appraised, and data on the proportion of patients gaining ≥ 15 Early Treatment Diabetic Retinopathy Study (ETDRS) letters in best-corrected visual acuity (BCVA), mean change in BCVA (ETDRS letters), and reduction in central macular thickness (CMT) (μm) were extracted and synthesized.Results: The systematic review identified 18 studies comprising randomized controlled trials, prospective studies, retrospective analyses, and observational studies. Anti-VEGF therapy demonstrated efficacy across all three conditions, with varying proportions of patients experiencing improvements in BCVA and reductions in CMT. Notably, the proportion of patients gaining ≥ 15 ETDRS letters ranged from 18.1% to 44.8% in DME, while mean changes in BCVA ranged from +4.2 letters to +21.4 letters in RVO-related ME and nAMD. Reductions in CMT ranged from 183.1 μm to 294 μm in DME and RVO-related ME.Conclusion: Anti-VEGF therapy represents a cornerstone in the management of DME, RVO-related ME, and nAMD, with significant improvements observed in BCVA and reductions in CMT across diverse patient populations. While our findings support the effectiveness of anti-VEGF therapy in improving ocular outcomes, further research is warranted to compare its efficacy with alternative treatment modalities and to elucidate its long-term safety profile.Keywords: outcomes, anti-VEGF, diabetic macular edema, retinal vein occlusion, neovascular AMD